Design, Synthesis and Discovery of N, N'‐Carbazoyl‐aryl‐urea Inhibitors of Zika NS5 Methyltransferase and Virus Replication. (7th January 2020) - Spizzichino, Sharon; Mattedi, Giulio; Lauder, Kate; Valle, Coralie; Aouadi, Wahiba; Canard, Bruno; Decroly, Etienne; Kaptein, Suzanne J. F.; Neyts, Johan; Graham, Carl; Sule, Zakary; Barlow, David J.; et al.
Abstract: The recent outbreaks of Zika virus (ZIKV) infection worldwide make the discovery of novel antivirals against flaviviruses a research priority. This work describes the identification of novel inhibitors of ZIKV through a structure‐based virtual screening approach using the ZIKV NS5‐MTase. A novel series of molecules with a carbazoyl‐aryl‐urea structure has been discovered and a library of analogues has been synthesized. The new compounds inhibit ZIKV MTase with IC50 between 23–48 μM. In addition, carbazoyl‐aryl‐ureas also proved to inhibit ZIKV replication activity at micromolar concentration. Abstract : Novel antivirals targeting ZIKA virus : The recent outbreaks of Zika virus (ZIKV) worldwide make the discovery of novel antivirals a priority. Using a structure‐based virtual screening approach we were able to identify and develop a novel series of carbazoyl‐urea derivatives that are able to inhibit the ZIKV NS5‐MTase as well as ZIKV replication at micromolar concentration.